Synergic effect between inorganic salts and gamma-Al2O3 for xylose dehydration to furfural - Fúnez Núñez, Inmaculada; García-Sancho, Cristina; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Serrano Cantador, Luis; Maireles-Torres, Pedro Jesús (My University, 2018)
Lignocellulosic biomass, with a high content of hemicellulose, is the main source of pentoses, from which biofuels and value-added chemicals can be produced. Amongst the latter, 2-Furfuraldehyde (furfural, FUR) is the only unsaturated organic compound prepared from carbohydrates, obtained by acid-catalyzed dehydration of xylose (XYL). Different acid solid catalysts have been studied as alternative to conventional mineral acids, which are employed in industry. In this work, the dehydration of XYL in a biphasic water:toluene system with a mesoporous γ-Al2O3 has been studied, and the effect of the presence of CaCl2 or MgCl2 in the reaction medium on the catalytic performance was evaluated. The presence of CaCl2 and the use of γ-Al2O3 in the reaction medium for xylose dehydration to furfural were studied and compared to the non-catalytic process, at 175 °C. In all cases, high conversion values were attained with respect to the non-catalytic process. γ-Al2O3 shows a high activity, with a XYL conversion of 96%, after 90 min of reaction, but the furfural yield was lower than expected due to alumina favored secondary reactions. Thus, high furfural yields were achieved by using CaCl2 even in absence of catalyst under these experimental conditions. However, considering that side reactions are favored at high temperatures, the catalytic process was studied with CaCl2 and γ-Al2O3 at 150 °C. At this lower temperature, a synergistic effect can be inferred between γ-Al2O3 and CaCl2, reaching values of XYL conversion and FUR yield of 99% and 59%, respectively, after only 30 min of reaction. Moreover, the effect of the addition of CaCl2 and MgCl₂ was compared (Fig. 3), adding the same number of moles, corresponding to 0.65 and 0.39 gsalt·gaq.sol., respectively. Although both salts improved the catalytic performance, CaCl2 is more beneficial than MgCl2. The reaction mechanism has been studied by 1H NMR.
Keywords: Biomasa; Biomass; Lignocelullose; Xylose; Furfural; Dehydration